8th Annual Conference of the California Society of the American Institute of Park Executives Inc. - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait showing the attendees of the 8th Annual Conference of the California Society of the American Institute of Park Executives Inc., held January 20-23, 1957 in San Jose, California.